The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnut.2022.873623
|View full text |Cite|
|
Sign up to set email alerts
|

Segmental Bioimpedance Variables in Association With Mild Cognitive Impairment

Abstract: ObjectiveTo examine the changes in body composition, water compartment, and bioimpedance in mild cognitive impairment (MCI) individuals.MethodsWe obtained seven whole-body composition variables and seven pairs of segmental body composition, water compartment, and impedance variables for the upper and lower extremities from the segmental multi-frequency bioelectrical impedance analysis (BIA) of 939 elderly participants, including 673 cognitively normal (CN) people and 266 individuals with MCI. Participants’ cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…In the data preprocessing, participants who had non-random missing data ( n = 18) and extreme results (sparse data points above or below three times the interquartile range were considered extreme points) for any parameter ( n = 8) were excluded from the analysis. According to the principle of multifrequency bioelectrical impedance analysis, correct impedance measurements should have lower values for higher frequencies (i.e., impedance at 1 kHz is greater than impedance at 5 kHz); therefore, observations that did not follow this pattern were excluded ( n = 91) ( 31 ). All of the participants answered the cold heat pattern questionnaire and were accordingly classified into the CP or non-CP groups.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the data preprocessing, participants who had non-random missing data ( n = 18) and extreme results (sparse data points above or below three times the interquartile range were considered extreme points) for any parameter ( n = 8) were excluded from the analysis. According to the principle of multifrequency bioelectrical impedance analysis, correct impedance measurements should have lower values for higher frequencies (i.e., impedance at 1 kHz is greater than impedance at 5 kHz); therefore, observations that did not follow this pattern were excluded ( n = 91) ( 31 ). All of the participants answered the cold heat pattern questionnaire and were accordingly classified into the CP or non-CP groups.…”
Section: Methodsmentioning
confidence: 99%
“…As peripheral regions such as the arm and leg have appreciable variances, whereas the vital central organs are strongly resisted by thermoregulatory mechanisms ( 35 ), the segmental variables for the body trunk were ignored in the analysis. Using these extremity bioimpedance variables, we computed the upper (lower) extremities variables by averaging the corresponding variables in the right and left arms (legs) as suggested in our previous publication ( 31 ). In this study, two R ratio variables for the upper and lower extremities (i.e., Ri_Re_upper and Ri_Re_lower) were computed such that the R ratio was the difference between the R at 250 kHz and that at 5 kHz divided by the R at 5 kHz ( Supplementary Table 1 ) ( 26 , 36 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a study reported positive correlations between muscle mass percentage and cognitive function measures such as attention and executive function ( Crespillo-Jurado et al, 2019 ). Recent research has also revealed associations between MCI and increased segmental water and lean mass in the lower extremities, as well as decreased resistance and reactance in the lower extremities ( Doan et al, 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, F. A. Author is with the to attain chemical and neurological balance inside human body [3][4][5]. Which implies the chances of hormone impelled indices to be indicators of human acumen.…”
Section: Introductionmentioning
confidence: 99%